Avaliação do conforto térmico com base em critérios normativos em apartamentos representativos do Programa Minha Casa Minha Vida em Maceió – AL. - Ferreira, Miryan Patricia Tenorio (2019)
The Minha Casa Minha Vida Program (PMCMV) was launched in 2009 with the intent of promoting social inclusion and overcome housing shortages and it was responsible for the construction of 30.780 housing unities in the City of Maceió between 2009 and 2014. In practice, the PMCMV acts in favor of private interests being characterized by a massive production that implies in inadequate thermal conditions. The aim of this work is to evaluate the thermal performance of a apartments building of the Minha Casa Minha Vida Program, located in the city of Maceió - AL. For this purpose, a relevant study case was defined in the context of the PMCMV production in the city of Maceio that consists of a 3 storey building in the Benedito Bentes neighborhood. Four unities were selected for the study, two on the ground floor (M002-TP e M007-TN) and two on the top floor (R202-CP e A207-CN), characterized as "favorable situation" and "unfavorable situation” due to insolation and ventilation. Air temperature monitoring and wind speed measurements were performed during the summer for the thermal perfomance evaluation. The monitoring data were used to identify the comfort zone limits according to the ASHRAE Standard 55 (2017) and the environment’s effective temperature through the effective temperature nomogram. Finally, the data were compared with the evaluations of NBR 15575 (simplified procedure) and RTQ-R (prescriptive method). The results indicate the influence of the solar orientation and floor of the unities and the internal environment’s use conditions in the evaluations. The east-facade unities registered the lowest amount of degree-hour of cooling and the lowest percentage of discomfort hours due to heat: 30,72% on the ground floor (M007-TN) and 37.54% on the top floor (A207-CN). These rooms were the ones that presented the best energy efficiency levels according to RTQ-: level C on both floors. The west-facade unities presented the highest temperatures and percentage of discomfort hours due to heat:57.45% on the ground floor (M002-TP) and 43.55% on the top floor (R202-CP). These rooms also presented the worst classifications according to the RTQ-R: levels D on the ground floor and level E on the top floor. It should be noted that the room M002-TP, that showed the highest percentage of discomfort hours, being the only room where the windows remained opened most of the time, without the protection of blinds, resulting in higher gains of heat due to direct insolation and smaller area for heat dissipation in compared to the top floor. The NBR 15575 evaluation for the typical summer day showed that the west-facade apartment on ground floor was the only room that did not achieve the minimal level. The measurement of wind speed indicated the potential for reduction of internal effective temperature at some places within the room. However, the evaluations of RTQ-R and NBR 15575 determine parameters for opening dimensions only, disregarding important aspects that aim to promote a good use of natural ventilation. Therefore, the divergences in the results of the different forms of evaluation are evident, as well as the fragility in the evaluation of some criteria such as, for example, the temperature of the typical summer day (NBR 15575) and the natural ventilation (NBR 15575 e RTQR), in terms of guaranteeing the user's thermal comfort.